Effective Atomic Number Determination of Rare Earth Oxides with Scattering Intensity Ratio - Turşucu, Ahmet; Demir, Demet; Döner, Pınar (HINDAWI LTD, 2013)
Effective atomic numbers (Z(eff)) of scientific samples (rare earth) were determined experimentally by scattering of 59.54 keV gamma photons from 5 Ci(241) Am annular radioactive source. The scattered gammaphotons were collected by using a high-resolution HPGe semiconductor detector placed at 167 degrees to the incident beam. This experiment was carried out on several elements in the atomic range 4 <= Z <= 82 for 59.54 keV incident photons. Photopeak efficiency and air and sample absorption corrections were performed on Rayleigh to Compton scattering intensity ratio; then the ratio was plotted as a function of atomic number and a fit curve was constituted. The effective atomic numbers of rare earth oxide samples were determined by this fit curve. Also, related parameters were determined by absorption technique with the same incident photon energy. Obtained values from this fit curve were compared to theoretical values and were found to closely agree with theoretical calculations.